Embedding equity into school mental health theory, research, and practice: An introduction to the special issue series. Issue 10 (16th February 2022) - Exner‐Cortens, Deinera; Gaias, Larissa; Splett, Joni W.; Jones, Janine; Walker, Whitney
Abstract: In this article, we present an introduction and overview for a two‐part special issue series focused on embedding equity into school mental health through theory, research, and practice. The papers in Part 1 of the special issue series cover critical topics for advancing equitable school mental health, including the centering of community and youth perspectives; a focus on reducing disproportionality in discipline practices; and details on equity‐focused interventions. In Part 2, papers focus on integrating race and racial equity into school mental health frameworks; integrating a racial equity lens into trauma‐informed school practices; addressing outcomes that have disproportionate impacts on youth of color; and exploring domains of injustice and oppression beyond racial inequity. We hope that the topics discussed in this special issue series move us towards providing equitable and just school mental health services for all children and youth.